2008
DOI: 10.1007/s10461-008-9385-1
|View full text |Cite
|
Sign up to set email alerts
|

Between Tradition and Change: Condom Use with Primary Sexual Partners Among Mexican Migrants

Abstract: The frequency of male Mexico-US migration has been associated with increased HIV risk for sexual partners awaiting their return in Mexico. This study examined the association between sexual partner characteristics and condom use among a sample of 354 male migrants from two Mexican municipalities. Migrants were interviewed about their past year's sex practices. Results indicated that migrants were more likely to use condoms with their non-spousal partners, partners with less education than the migrant, and part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…One study in Thailand revealed that male labour migrants’ condom use depended on the female partner type: 79% always used condoms with sex workers, 51% always used condoms with non-regular partners, and 1% always used condoms with their regular partner (Ford and Chamrathrithirong 2007). Studies of male labour migrants in Mexico and Zambia showed that migrants used condoms less with partners who they believed to be “clean,” and more with partners who were unknown (Bond and Dover 1997; Caballero-Hoyos et al 2008). Notably, however, few studies have examined HIV risk and protection in relationships from both the male migrants’ and female regular partners’ perspectives (Hirsch et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One study in Thailand revealed that male labour migrants’ condom use depended on the female partner type: 79% always used condoms with sex workers, 51% always used condoms with non-regular partners, and 1% always used condoms with their regular partner (Ford and Chamrathrithirong 2007). Studies of male labour migrants in Mexico and Zambia showed that migrants used condoms less with partners who they believed to be “clean,” and more with partners who were unknown (Bond and Dover 1997; Caballero-Hoyos et al 2008). Notably, however, few studies have examined HIV risk and protection in relationships from both the male migrants’ and female regular partners’ perspectives (Hirsch et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This has important implications for their wives or partners in California and Mexico, who, because of traditional feminine roles in Mexico, and the associated low degree of power, may have limited ability to negotiate sexual practices with their partners, such as condom use, or to discuss men's previous sexual histories while in the USA (Magis-Rodriguez et al 2004). Numerous other studies have confirmed that female partners of Mexican men who travel to the USA may be unknowingly at high risk for STIs, including HIV/AIDS (Hirsch et al 2002;Brammeier et al 2008;Caballero-Hoyos et al 2008). As our study showed, even though Mexican immigrant women in California are making strides towards equality in the household, from the male participant's perspectives, it remains unclear how much power female partners actually have in the realm of reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…In general, condoms are used infrequently (Apostolopoulos et al, 2006;Brammeier et al, 2008;Caballero-Hoyos et al, 2008). Men also reported lower condom use specifically with girlfriends (Pulerwitz et al, 2001), CSWs (Magana, 1991), and their wives (Hernandez-Rosete et al, 2008).…”
Section: Relative Risk Lifestyle Behaviors and Choicesmentioning
confidence: 99%
“…In a survey of 354 migrants from two municipalities in western Mexico, gender views were constructed from a combination of patriarchal ideologies imparted during childhood and ideologies of change learned during the migration experience (Caballero-Hoyos et al, 2008). Sowell et al (2008) found that women in Mexico accepted the dominance of their husbands in all aspects of their lives and experienced powerlessness on the basis of both economic factors and cultural traditions.…”
Section: Resource Availability Socioeconomic Resourcesmentioning
confidence: 99%